How the Level of Education Impacts Consumers with Green Trust: Authenticity and Physical Attractiveness on Fire Products - Aswar, Nurul Fadilah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to analyze how brand authenticity, physical attractiveness, and green trust, depending on the level of education, influence consumer purchase decisions at Fore Coffee. The study employs a causal-comparative research approach, incorporating structural equation modeling (SEM) analysis. We used purposive sampling as the sampling technique. This resulted in a sample size of 100 respondents. The study collected primary data by distributing an online questionnaire via Google Forms to respondents who met the study's criteria. The findings of the research indicate that the level of education and brand authenticity significantly influence both green trust and purchase decisions. Additionally, the physical attractiveness of the product impacts purchase decisions through the lens of green trust. The study concludes that the values of authenticity, the physical attractiveness of the product, and the consistency of transparent sustainability claims shape purchase decisions, with levels of education and green trust playing a crucial role.